Parental attitudes of mothers raising sons with Crohn’s disease - Weryszko, Małgorzata; Izabela (Kwartalnik Naukowy Fides et Ratio, 2022)
The article describes the issues and presents research on parental attitudes of mothers towards somatically ill children. The analysis of the issue includes the mother’s point of view as well as the child’s point of view. The conducted research shows a relationship between the assessment of parental attitudes of mothers and their assessment of their sons suffering from Leśniowski-Crohn’s somatic disease. They point to the differences in the perception of mothers’ parental attitudes from these two perspectives. They also show the relationship between the child’s age and the mother’s attitude. The study included 30 mothers and their 30 teenage sons suffering from Leśniowski-Crohn’s disease.